Kultura komunikacji urzędowej - Kołodziejek, Ewa (Poznańskie Spotkania Językoznawcze, 2014)
The topic of considerations is the language communication culture of varied official texts. The author evaluates the level of linguistic competence of the authors of ministerial documents published on the Web pages of those institutions. She also reports on the attitudes of the senders and addressees of official texts forming the subject of discussion of the First Congress of the Official Language (Pol. I Kongres Języka Urzędowego). She contends, drawing on her personal experiences, that translators engaging in the translation of EU texts into Polish demonstrate utmost care for wording and communicability of official documents. Moreover, translators are held up as a model of care for high level of culture of office communication.